God, Evil, Freedom. Reception and Interpretation of Dostoevsky in Luigi Pareyson and his Heirs - Carrieri, Alessandro (Labyrinth, 2021)
The essay aims to focus on reception and interpretation of Dostoevsky in the thought of Luigi Pareyson (1918-1991) and his heirs, who have developed a deep and original theoretical reading of Dostoevsky's work, able to bring out not only its ethical stance, but most of the essential aspects of his thought, and to investigate its current relevance. The reflection of Pareyson – who promoted the introduction of Dostoevsky's thought into the academic circles of Turin, being convinced that philosophy cannot avoid confronting the issues it explores – consists of three main moments: the experience of good and evil, the experience of freedom and the experience of God. Starting from consideration of Dostoevsky's characters as ideas, Pareyson proposes a new and coherent philosophical interpretation of his work, which can undoubtedly be compared to those of Ivanov, Berdjaev, Evdomikov, Šestov. His observations around the Legend of the Grand Inquisitor and the "refutation of Ivan" – which, according to him, constitute the most significant and theoretically prolific moments of Dostoevsky's production – seem unaffected by the flow of time and could still represent a valuable and indispensable contribution to the understanding not only of the great Russian author, but of human nature itself.